Diode laser-assisted endoscopic dacryocystorhinostomy: A comparison of three different combinations of adjunctive procedures - Doğan, Remzi; Meriç, Ayşenur; Özsütcü, Mustafa; Yenigün, Alper (Springer, 2013)
Chronic dacryocystitis is a frequently encountered condition which can be corrected by dacryocystorhinostomy. Today, the diode laser is increasingly put to use in such corrective operations. This study aims to answer the questions of which adjunctive procedures and which combinations of such procedures are necessary and effective in securing more successful outcomes in diode laser dacryocystorhinostomy. This prospective randomized study included eighty patients (13 male, 67 female) who underwent dacryocystorhinostomy in our hospital during the 2 year period of January 2009-January 2011. The patients were selected consecutively and were randomly allocated to three groups. Group 1 (30): diode laser + mitomycin C + silicone intubation; Group 2 (27): diode laser + silicone intubation; Group 3 (23): diode laser + mitomycin C. All patients were evaluated postoperatively on day 1, week 1, and on the 1st, 3rd, 6th, 12th, 18th, and 24th months. The postoperative evaluation consisted of preoperative and postoperative ostium measurements, recording postoperative complications, and calculating and comparing success rates and operative times. The mean ages of the patients were 63.4 for Group 1, 60.7 for Group 2, and 61.8 for Group 3. No statistically significant difference was found among the groups regarding pre- and postoperative ostium measurements. The success rates were 84.3, 80, and 76.9 % for Groups 1, 2, and 3, respectively. Complications noted in Group 1 were restenosis (3), premature silicone tube loss (1), development of granulation tissue (3), synechia (2), infection (2), and hemorrhage (3). Those for Group 2 were restenosis (5), premature tube loss (2), granulation (8), synechia (6), infection (3), and hemorrhage (4). Group 3 had 6 cases with stenosis, 5 with granulation, 3 with infection, 6 with synechia, and 5 with hemorrhage. The operative times of the groups were 25.5, 15.3, and 18.1 min, respectively, for Group 1, 2, and 3. All three groups had statistically significant differences regarding the duration of surgery, with p < 0.001, p < 0.001, and p = 0.002 for Group 1 and 2, Group 1 and 3, and Group 2 and 3, respectively. Our study showed that when diode laser DCR was combined with bicanalicular silicone intubation and intraoperative mitomycin C application, those adjunctive procedures, while increasing operative time, enhanced the success rate and diminished complications as compared to diode laser plus intubation and/or diode laser plus mitomycin C.
WOS: 000321286600012
PubMed ID: 23334177
Keywords: Chronic Epiphora; Diode Laser Dacryocystorhinostomy; Silicone Intubation Tube; Mitomycin C